1989
DOI: 10.1073/pnas.86.2.587
|View full text |Cite
|
Sign up to set email alerts
|

Association between a specific apolipoprotein B mutation and familial defective apolipoprotein B-100.

Abstract: Familial defective apolipoprotein (apo) B-100 is a genetic disease that leads to hypercholesterolemia and to an increased serum concentration of low density lipoproteins that bind defectively to the apoB,E(LDL) receptor. The disorder appears to result from a mutation in the gene for apoB-100. Extensive sequence analysis of the two alleles of one subject heterozygous for the disorder has revealed a previously unreported mutation in the codon for amino acid 3500 that results in the substitution of glutamine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
218
0
16

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(236 citation statements)
references
References 29 publications
2
218
0
16
Order By: Relevance
“…The latter situation usually results in a mild or severe form of hypercholesterolemia together with an increased risk for early onset atherosclerosis [10,11]. In contrast to LDLR, only a small number of functional mutations have been identified in APOB gene such as R3500Q [12], R3500 W [13], and R3531C [14]. There are very limited data regarding LDLR and APOB gene mutations in Iranian population [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The latter situation usually results in a mild or severe form of hypercholesterolemia together with an increased risk for early onset atherosclerosis [10,11]. In contrast to LDLR, only a small number of functional mutations have been identified in APOB gene such as R3500Q [12], R3500 W [13], and R3531C [14]. There are very limited data regarding LDLR and APOB gene mutations in Iranian population [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…APOB mutations have been estimated to account for 1-5% of patients with FH, and are inherited in an autosomal dominant manner [65,66]. From APOB, apo B-100 is synthesized exclusively in the liver as one of the two main protein isoforms, and is a major constituent of LDL and VLDL.…”
Section: Apobmentioning
confidence: 99%
“…All these children were negative for the six previously known FC Mutations in the LDL receptor gene (Simard et al, 1994) and were then screened for the three mutations. The ApoB 3500 mutation (Soria et al, 1989) was not found in any of the 15 adult FH patients or in any of the 48 children, as determined by the assay that was previously described (Hansen et al, 1991). Additional 100 normocholesterolemic FC men were also screened for the C152W and C347R mutations in order to exclude that these mutations are not linked polymorphisms.…”
Section: Methods Subjectsmentioning
confidence: 99%